PEMANFAATAN VIDEO DOKUMENTER HASIL KAJIAN PENINGGALAN SEJARAH (KPS) SEBAGAI MEDIA PEMBELAJARAN SEJARAH - Yuniati, Yuniati (Indonesian Journal of History Education, 2015)
The purpose of this study: (1) To determine the video documentary PPP results can be used as a medium of learning history. (2) To know the history of education study program student class of 2011 in the documentary video Utilizing the results of KPS as a learning medium. (3) Efforts are being made to improve the course KPS department. Based on data analysis and discussion, it can be deduced as follows: Video documentary PPP results can be used as a medium of learning, whether used as an opener, the core and the enrichment of the teaching of history. Student education department of history angakatan 2011 has memanfaatakan KPS documentary video as a medium in the classroom when executing Practice Field Experience history in 2014. The Department has made every effort in order to develop and improve the field of PPP lectures become better and can achieve the goals of PPP and produce as expected. Â